V34I and V34A substitutions within the factor XIII activation peptide segment (28-41) affect interactions with the thrombin active site - Trumbo, Toni A.; Maurer, Muriel C. (Thrombosis and Haemostasis, 2003)
In the blood coagulation cascade, thrombin helps activate Factor XIII by cleaving the Factor XIII Activation Peptide at the R37-G38 peptide bond. The common polymorphism V34L yields a Factor XIII that is more easily activated than the wild-type enzyme. Peptides based on the Factor XIII (28-41) ( 28TVELQGVVPRGVNL41) sequence serve as an important model system for evaluating how to regulate thrombin activation of Factor XIII and subsequently fibrin clot character. Kinetic and NMR (1D proton line broadening and 2D transferred NOESY) studies have revealed that the P4-P1 region of the activation peptides is critical for binding to the thrombin surface. These results have led to an interest in exploring two new mutations at the P4 position including V34I and V34A. The V34I peptide was found to have the lowest Km of the peptides studied. However, unlike the V34L peptide, there are no P4 to P2 interactions observed in the transferred NOESY spectrum. The Leu thus promotes a bound conformation that cannot be achieved with the similar amino acid Ile. The V34A peptide exhibited a decrease in Km but also a substantial decrease in kcat. With this smaller amino acid, 1D proton line broadening NMR studies indicate that further contact of the Q32 residue with the thrombin surface is now possible. From these studies, valuable kinetic and structural information is being obtained to characterize interactions between thrombin and the Factor XIII activation peptide.Theme paper: Part of this paper was originally presented at the joint meetings of the 16th International Congress of the International Society of Fibrinolysis and Proteolysis (ISFP) and the 17th International Fibrinogen Workshop of the International Fibrinogen Research Society (IFRS) held in Munich, Germany, September, 2002.
Keywords: Factor XIII; thrombin; V34L polymorphism; kinetics; transferred NOESY